Revolutionizing Sales and Trading: Sino Aquarium Upgrades to Computerized System for Better Performance: Merevolusi Penjualan dan Perdagangan: Sino Aquarium Upgrade ke Sistem Komputerisasi untuk Performa Lebih Baik - Sujadi, Rizal Iman; Astutik, Ika Ratna Indra (Universitas Muhammadiyah Sidoarjo, 2023)
In today's information age, various types of businesses, especially those in sales and trading, are highly competitive. Therefore, every company strives to improve its performance in various ways, including creating an information system to manage its business. Such a system can connect all departments involved in managing the business, making it easier and more organized to perform tasks with great detail. Sino Aquarium, a store selling ornamental fish, still uses a manual system and wants to switch to a computerized system. Computers are expected to meet the store's needs as a highly productive tool for managing data quickly, accurately, and efficiently. Therefore, Sino Aquarium, which operates in a highly trading-dependent field, needs a computer as a tool to manage data and obtain necessary information quickly, accurately, and precisely. Highlights: 1. In today's highly competitive business environment, companies strive to improve their performance through various means, including implementing information systems. 2. Implementing an information system can connect different departments involved in managing the business, resulting in better organization and task performance. 3. Sino Aquarium recognizes the importance of a computerized system to manage data accurately and efficiently, considering its highly trading-dependent field.